MAPPING MANGROVE COVER CHANGE USING PLANETSCOPE DATA (2017-2022) IN QUANG YEN TOWN, QUANG NINH PROVINCE TOWARD SUSTAINABLE MANGROVE MANAGEMENT - Hai Hoa, Nguyen; Duy Quang, Pham; Van Truong, Vu; Phu Tuan, Le (Journal of Forestry Science and Technology, 2022)
Mangroves are found along shallow shorelines with modest slope where they receive freshwater runoff and nutrients from rainfall. They have been globally recognized as their vital functions in preventing coastal erosion, mitigating effects of wave actions and protecting coastal habitats from extreme coastal events. By using PlanetScope imageries (3mx3m), the study has constructed the spatial distribution of mangrove forests from 2017 to 2022. This study defined and used the CMRI thresholds for coastal land covers (CMRI value > 0.835 for mangrove forests, CMRI <0.835 for non-mangrove forests). The overall accuracies assessments of land covers in 2022 (96.4% of accuracy, Kappa coefficient of 0.92) and land covers in 2017 (94.1% of accuracy, Kappa coefficient of 0.87) have confirmed using PlanetScope images were very reliable for mapping temporal changes in land use/cover and mangrove covers in Quang Yen town. The study also showed that mangrove forests in Quang Yen town decreased by 443.1 ha in 2022 (2745.1 ha) compared to 2017 (3114.4 ha) and main drivers for mangrove deforestation and degradation during the period of 2017 - 2022 were aquaculture development, socioeconomic development and other land use conversions. The study highly suggests that using PlanetScope imagery should be applied to estimate AGB and C-stocks of mangrove forests in Quang Yen town and expanded in other similar coastal areas in Quang Ninh province. A blue carbon approach should be taken into account toward sustainable mangrove management in Quang Yen.